Profitable and sustainable farming of poplar for Indian farmers - Chavan, S.B.; Sirohi, Chhavi; Dhillion, R. S. (Indian Farming, 2026)
Poplar (Populus deltoides) has emerged as a flagship species for agroforestry in the Indo-Gangetic Plains of India, offering both economic and ecological benefits. Its fast growth, deciduous nature, and compatibility with rabi crops make it highly suitable for integration with traditional farming. Scientific nursery practices, Entire Transplants (ETP) selection, and improved planting techniques ensure high survival and productivity. Poplar-based agroforestry systems generate substantial income within short rotations while supporting diversified cropping. This article provides need-based, practical guidance covering the complete package of practices—from nursery establishment to harvest—supporting scientific cultivation and enhanced productivity for farmers and nursery practitioners.